Green supply chain management practices in manufacturing sector in Malaysia - Ruban, Nitia; Abdullah, Rohani (2012)
The purpose of this paper is to determine the best green practices that integrate environmental concerns into supply chain management among the industries in Malaysia. A detailed review is used to sort out the literature and develop the research direction of the study.The review is focused on development of GSCM in Malaysia including all those researchers which is relevant to environmental and social sustainability towards operation management and supply chain.